Evaluation Of Total Phenol, Flavonoids, Antioxidant Activity And Gc-Ms Of Ethanol Extract Of Moringa Oleifera Whole Leaves - Parveen, Moon Sahara; Gousuddin, Mohammad; Abidin, Suhaili Zainal (Journal of Neonatal Surgery, 2025)
The medicinal plant known as moringa (Moringa oleifera Lam) is also a nutrient source. It contains antioxidant properties and is heavy in protein, fatty acids, minerals, and comparatively high levels of polyphenol chemicals. Finding out about the ethanol extract of Moringa leaves' secondary metabolites, total phenol content, total flavonoids, antioxidant activity, and GC-MS is the goal of this study. The colorimetric method was used to quantify total flavonoids, whereas the Folin Ciocalteu method was used to determine total phenol. The DPPH (2,2-diphenyl-i-picrylhydrazyl) technique was used to measure the antioxidant activity at a wavelength of 520 nm. Flavonoids, phenols, tannins, saponins, alkaloids, and steroids were found in the ethanol extract of Moringa leaves, according to the results. 9.1983 ± 0.00132 GAE/g extract was the total amount of phenol in the ethanol leaf extract. The flavonoid concentration in the extract was 0.3474 ± 0.00195 QE mg/mL. Moringa leaf ethanol extract is categorized as having moderate antioxidant activity due to its IC50 of 27.79 µg/mL. Eleven chemicals were found in the extract according to GC-MS analysis, with three compounds found in each peak. 30.15% methyl (11E)-11-octadecenoate, 19.16% cis-octadecenoic acid or cis-oleic acid, and 17.67% methyl-14-methyl pentadecanoate. Because the majority of the chemicals on the list are bioactive and have therapeutic qualities, the use of the traditional Moringa oleifera plant in the development of new treatments is further supported.